2021
DOI: 10.3390/jcm10184276
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory COVID-19 Patients Treated with Lactoferrin as a Supplementary Antiviral Agent: A Preliminary Study

Abstract: SARS-CoV-2, an enveloped, single-stranded RNA virus causing COVID-19, exerts morbidity and mortality especially in elderly, obese individuals and those suffering from chronic conditions. In addition to the availability of vaccines and the limited efficacy of the first dose of vaccine against SARS-CoV-2 variants, there is an urgent requirement for the discovery and development of supplementary antiviral agents. Lactoferrin (Lf), a pleiotropic cationic glycoprotein of innate immunity, has been proposed as a safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 58 publications
4
34
0
Order By: Relevance
“…Accordingly, we documented a significantly reduced mean time to rRT-PCR SARS-CoV-2 RNA negative conversion in a liposomal bLf-treated group compared to SOC-treated and untreated patients, suggesting a favoring of gradual viral clearance and clinical symptoms recovery with a potential decrease in the risk of transmission and contagion. This result is in agreement with the data obtained by Rosa et al [58] in a survey based on reallife clinical practice conducted on ambulatory asymptomatic, paucisymptomatic, and moderate symptomatic COVID-19 patients treated with bLf, alone or as a supplementary agent. BLf oral administration, unloaded in liposomes, induces a time to SARS-CoV-2 RNA negativization similar to that observed with liposomal bLf (15 versus 14.25 days).…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we documented a significantly reduced mean time to rRT-PCR SARS-CoV-2 RNA negative conversion in a liposomal bLf-treated group compared to SOC-treated and untreated patients, suggesting a favoring of gradual viral clearance and clinical symptoms recovery with a potential decrease in the risk of transmission and contagion. This result is in agreement with the data obtained by Rosa et al [58] in a survey based on reallife clinical practice conducted on ambulatory asymptomatic, paucisymptomatic, and moderate symptomatic COVID-19 patients treated with bLf, alone or as a supplementary agent. BLf oral administration, unloaded in liposomes, induces a time to SARS-CoV-2 RNA negativization similar to that observed with liposomal bLf (15 versus 14.25 days).…”
Section: Discussionsupporting
confidence: 93%
“…In another clinical study in Tor Vergata University Hospital (Rome, Italy), oral and intranasal liposomal bLf was administered in asymptomatic and mild-to-moderate COVID-19 patients compared to standard of care (SOC)-treated and untreated COVID-19 patients ( 14 ). In agreement with previously reported data ( 13 ), significantly less mean time to SARS-CoV-2 RNA negative conversion was detected in a liposomal bLf-treated group compared to SOC-treated and untreated patients (14 versus 27 days), with fast clinical symptoms recovery ( 14 ). Moreover, in liposomal bLf-treated patients, a significant reduction in serum IL-6, ferritin and D-dimers levels was shown ( 14 ).…”
Section: Introductionsupporting
confidence: 92%
“…Based on preclinical studies, Rosa and colleagues developed a recent study to assess the efficacy of oral bLf on ambulatory COVID-19 patients ( 13 ). Results of this study revealed that the time required achieving SARS-CoV-2 RNA negativization in bLf-treated patients was lower compared to that reported in bLf untreated patients (15 versus 24 days).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that asymptomatic, pauci-symptomatic, and moderate COVID-19 lactoferrin-treated patients show faster virus negativization and more rapid clinical recovery than untreated patients. Furthermore, Lactoferrin treatment is safe and well tolerated in all treated patients [ 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%